PROYEKSI JADWAL DAN BIAYA PADA PELAKSANAAN PROYEK PEMBANGUNAN BANGUNAN ATAS JEMBATAN BETON - I Ketut Nudja S. (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2018)
ABSTRACT Cost and time control is the heart of activities for contractors, because of this effort the company can earn profits and avoid risks, so that the survival of the company can be maintained and developed. At the implementation stage the dominant control element is carried out to find out whether time and costs deviate, according to or have exceeded the plan. After knowing the above conditions, it is necessary to project how much time and costs are needed again. The purpose of the schedule and cost projections in the implementation of the building construction project on a concrete bridge is to be able to find out how much time and costs are needed to complete the project, so that it is useful in making decisions. The results of the calculation show the estimated total project cost (Estimate All Cost - EAC) is obtained for = IDR3,671,279,379.50, from the planned IDR2,722,001,580.00. For the total project time estimate (Estimate All Schedule - EAS) is obtained = 112 days, taking the largest value, from the 91 day plan. Keywords: cost, EAC, EAS, time